How Environment knowledge, Social Influences, and Attitude Impact The Millenial Generation’s Purchase Intention in Green Products Through Attitude? - Purboyo, Purboyo; Lamsah, Lamsah; Zulfikar, Rizka; Wahyuni, Amalia (Publisher Cv. Inara, 2022)
Thistime the world is covered by environmental issues in the form of climate change, the use of natural resources that do not pay attention to the environment, and the sale of products that are not environmentally friendly, and currently the millennial enerasi is a generation that is a lot in Indonesia with a proportion of 33.75%, as a generation that is quite large, the millennial generation in the future has a considerable answer to the issue. environmental preservation and use of green products. The purpose of this study is to find out the influence of environmental knowledge variables and social influence variables on green product buying intentions, both directly and indirectly through attitude variables as mediation variables. This type of quantitative research is used by collecting data using questionnaires on millennial respondents totaling 150 respondents. The data is analyzed using the SEM PLS approach. The results showed that variable social influences and attitudes had a positive and significant effect on the intention to buy green products. Variable environmental knowledge and social influences have a positive and significant effect on attitudes. While the variable of environmental knowledge does not have a significant effect on the intention to buy green products. The interesting result is that mediation gives the result that variables of environmental knowledge and variables of social influence have a positive and significant effect on the intention of buying green products through attitude variables as mediation variables.